Estimation of Stature from Arm Span: A Prospective Study Among Medical Students of Rangpur Medical College (Journal of Rangpur Medical College, 2022)
Background: Arm span is one of the most reliable body parameters for predicting the stature of an individual. It is useful in an age-related loss in stature and in identifying individuals with disproportionate growth abnormalities and skeletal dysplasia.Objectives: The present study was undertaken to determine whether there is any correlation between stature and arm span and estimate stature from arm span by using multiplication factor and assess the effectiveness of the above estimation by comparing the ‘estimated’ values with the measured values.Methods: This is a cross-sectional analytical study done in the Department of Anatomy, Rangpur Medical College, Rangpur, from January to December 2018 on purposively selected 700 medical students (350 male and 350 female). Arm span along with their stature was measured directly from the subjects by using an anthropometric technique by a measuring tape. Multiplication factors were estimated for estimating stature and comparison were made between measured and estimated stature using paired “t” test.Results: The mean normal value of arm span was 170.48±7.38 cm in males and 156.13±5.98 cm in females and the stature was 168.93±0.06 cm in males and 156.23±0.05 cm in females. The multiplication factor was estimated for the same hand measurements with the stature. A significant positive correlation was found in the case of arm span with stature.Conclusion: Arm span is a valid measure of stature for both adult males and females.J Rang Med Col. September 2022; Vol. 7, No. 2:47-51